Successful treatment of remnant gastric cancer with afferent loop syndrome managed by percutaneous transhepatic cholangial drainage followed by elective gastrectomy: a case report - Shu Aoyama; Masaaki Motoori; Yasuhiro Miyazaki; Tomoki Sugimoto; Yujiro Nishizawa; Hisateru Komatsu; Akira Inoue; Yoshinori Kagawa; Akira Tomokuni; Kazuhiro Iwase; Kazumasa Fujitani (Surgical Case Reports)
Abstract Background There are only few reported cases of remnant gastric cancer with concomitant afferent loop syndrome. Emergency surgery is the standard treatment strategy for this disease. However, some afferent loop syndrome cases, especially those with complete obstruction, can lead to a septic state, which makes performing emergency surgery risky. We describe a case of remnant gastric cancer with complete afferent loop obstruction, which was successfully managed by radical surgery following percutaneous transhepatic cholangial drainage of the afferent loop. Case presentation A 71-year-old man presented with nausea and abdominal discomfort. When he was 27 years old, he had undergone distal gastrectomy for a benign gastric ulcer, with gastrojejunostomy (Billroth II reconstruction). Abdominal computed tomography revealed thickening of the anastomosis site and significant dilation of the afferent loop. Gastrointestinal fiberscopy revealed advanced remnant gastric cancer at the anastomosis site, and the stoma of the afferent loop was completely obstructed. We diagnosed the patient with remnant gastric cancer with afferent loop syndrome. Percutaneous transhepatic cholangial drainage was performed twice before surgery to decompress the afferent loop. This provided more time for the patient to recover. Radical surgery of total remnant gastrectomy and Roux-en-Y reconstruction were performed electively. There were no severe postoperative complications. The patient died 8 months following the operation owing to peritoneal dissemination recurrence. Conclusion We encountered a case of remnant gastric cancer with afferent loop obstruction, which was successfully managed by radical surgery following decompression of the afferent loop by percutaneous transhepatic cholangial drainage. Percutaneous transhepatic cholangial drainage effectively managed the afferent loop syndrome, resulting in the safe performance of elective surgery.